Resveratrol Ameliorates Glucocorticoid-Induced Bone Damage in a Zebrafish Model - Luo, Qun; Liu, Shengbo; Xie, Liming; Yu, Yongjie; Zhou, Limin; Feng, Yuzhen; Cai, De (Frontiers in Pharmacology, 2019)
Resveratrol (Res) is a multi-functional polyphenol compound that has protective functions in cardiovascular and neurodegenerative diseases. This study aimed to determine the effect of Res on osteogenic differentiation and bone mineralization in zebrafish (Danio rerio) with dexamethasone (Dex)-induced bone damage. Our results showed that Dex exposure (15 μmol/l) decreased the green fluorescence areas and the integrated optic density (IOD) values in the skull bones of zebrafish larvae of the TG(SP7:EGFP) strain in a dose-dependent manner (p < 0.01). Furthermore, Dex exposure decreased the alizarin red S-stained areas (bone mineralization area) in the skeleton and spinal bones of zebrafish larvae of the AB strain in a dose-dependent manner (p < 0.01). By contrast, Res treatment (150 μmol/l) significantly increased both the green fluorescence and bone mineralization area in Dex-exposed zebrafish larvae. Thus, our data show that Res improves bone mineralization after glucocorticoid-induced bone damage in a zebrafish model. Res may be a candidate drug for the prevention of osteoporosis.